2013
DOI: 10.7150/ijms.6014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Procalcitonin Levels in Predicting Ascitic Fluid Infection in Hospitalized Cirrhotic and Non-cirrhotic Patients

Abstract: Objective: To determine the role of serum procalcitonin levels in predicting ascites infection in hospitalized cirrhotic and non-cirrhotic patients.Methods: A total of 101 patients (mean age: 63.4±1.3, 66.3% were males) hospitalized due to cirrhosis (n=88) or malignancy related (n=13) ascites were included in this study. Spontaneous bacterial peritonitis (SBP, 19.8%), culture-negative SBP (38.6%), bacterascites (4.9%), sterile ascites (23.8%) and malign ascites (12.9%) groups were compared in terms of procalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 31 publications
6
59
0
Order By: Relevance
“…Ascitic fluid culture examination is time consuming (24-48h) which delays the diagnosis and treatment. Therefore, the identification of clinical and laboratory parameters for the early diagnosis of SBP would be of special interest 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Ascitic fluid culture examination is time consuming (24-48h) which delays the diagnosis and treatment. Therefore, the identification of clinical and laboratory parameters for the early diagnosis of SBP would be of special interest 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Five of 18 included studies were prospective [17, 18, 22, 23, 25], and 13 studies were retrospective in design [1921, 24, 26–34]. All studies had clearly defined inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies [2123, 25–27, 29–32, 34] had reported accuracy parameters on serum PCT in cirrhotic patients. The pooled sensitivity and specificity were 0.86 and 0.94 respectively, and the AUROC was 0.91 (95% CI: 0.89-0.94), indicating that serum PCT also had acceptable predictive performance in cirrhotic patients.…”
Section: Resultsmentioning
confidence: 99%
“…As the liver is believed to be a key source of PCT, there were initially concerns that hepatic impairment may result in downregulated serum PCT levels. Although, this was not proven to be the case [84] , and early reports were encouraging about the use of PCT in the diagnosis of SBP, its potential role remains currently unclear as several studies provided conflicting results [85][86][87][88][89][90][91][92][93] . A solution has been proposed with the use of an ultra-sensitive PCT assay [87] , and possible explanations for the discrepancies noted between studies include higher baseline levels in patient with alcoholic [94] or specific viral-related [95] causes of cirrhosis and the presence of other bacterial infections [96] .…”
Section: Calprotectin -Procalcitonin -Anti-neutrophil Cytoplasmic Antmentioning
confidence: 99%